STUDI TENTANG PERSEPSI MAHASISWA TERHADAP PELAKSANAAN TUGAS DEWAN PENGAWAS KPK DALAM UU NO. 19 TAHUN 2019 DI UNIVERSITAS RIAU PEKANBARU - May Sri Astuti; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the birth of legal political products, namely UU No. 19 year 2019 the Second Amendment to UU No. 30 year 2002 concerning the Corruption Eradication Commission. In UU No. 19 year 2019, there is a Supervisory Board tasked with overseeing KPK Leaders and Employees in carrying out their duties. As a result, there has been much speculation in the community that says the KPK Supervisory Board will hinder the KPK's performance. The formulation of the problem in this study is how the students' perceptions of the implementation of the KPK Supervisory Board duties in UU no. 19 year 2019 at Universitas Riau Pekanbaru. The purpose of this study was to determine students' perceptions of the implementation of the KPK Supervisory Board duties in UU no. 19 year 2019 at Universitas Riau Pekanbaru. The benefit of research results for students is to increase knowledge about student perceptions of the implementation of the KPK Supervisory Board duties in UU No. 19 year 2019 at the University of Riau. The research method used is descriptive quantitative, the data collection instruments used in this study were questionnaires and interviews which consisted of 20 questions with 6 indicators. The population in this study were undergraduate students (S1) at the University of Riau. The sampling technique in this study used quota sampling and incidental sampling. Based on the results of the research that has been done, the results of the calculation of respondents who answered